Analisis Longsor Cililin Dan Model Pengupayaan Kestabilan Lerengnya - -, Wisyanto (Jurnal Sains dan Teknologi Indonesia, 2014)
Landslides have occurred in various places in Indonesia. Likewise with West Java, there were many regions that has experienced repeated landslides. Having many experience of occurrences of landslides, we should have had a good landslide risk reduction program. Indeed, the incidence of landslides depends on many variables. Due to that condition, it may that a region would have different variable with another region. So it is impossible to generalize the implementation of a mitigation technology for all areas prone to landslides. Research of the Cililin's landslide is to anticipate the next disasters that may happen in around the area of 2013 Cililin Landslide. Through observation lithological conditions, water condition, land cover and landscape, as well as consideration of wide dimension of the building footing, the distance of building to the slopes and so forth, it has been determined some efforts of disaster risk reduction in the area around the landslide against the occurrence of potential landslide in the future.Bencana tanah longsor telah terjadi di berbagai tempat di Indonesia. Demikian halnya dengan Jawa Barat, tidak sedikit daerahnya telah berulang kali mengalami longsor. Seharusnya dengan telah banyaknya kejadian longsor, kita mampu mengupayakan program penurunan risiko longsor secara baik. Memang kejadian longsor bergantung pada banyak variabel, dimana dari satu daerah dengan daerah yang lain akan sangat memungkinkan mempunyai variabel yang berbeda, sehingga tidak mungkin kita membuat generalisasi penerapan suatu teknologi mitigasinya untuk semua daerah rawan longsor. Penelitian longsor di Cililin dilakukan untuk mengantisipasi terjadinya bencana di sekitar daerah Longsor Cililin 2013 yang lalu. Melalui pengamatan kondisi litologi, keairan, tutupan lahan dan bentang alam yang ada, serta pertimbangan akan dimensi luas pijakan bangunan, jarak batas bangunan dengan lereng dan lain sebagainya, telah ditentukan beberapa upaya penurunan risiko bencana di daerah sekitar longsor terhadap potensi kejadian longsor dimasa mendatang.Keywords:Ã‚Â Landslide, risk reduction, footing of building, Cililin